The role of authentic materials in improving communicative competence among Malaysian Polytechnic Students - Ibrahim, Liyana; Muhamad Affendi, Norliyana Bau (Jurnal Penyelidikan Sains Sosial, 2025)
This study explores the role of authentic materials in enhancing communicative competence among Malaysian polytechnic students, focusing on students' perceptions and the specific challenges they encounter. Grounded in Communicative Language Teaching (CLT) principles, the research employed a qualitative, phenomenological approach using open-ended questions to capture the lived experiences of ten diploma students from a Malaysian polytechnic. The findings reveal that authentic materials such as songs, movies, and real-life dialogues increase learner engagement and motivation and facilitate the development of core communicative skills, including listening, pronunciation, and accent awareness. These materials bridge the gap between classroom instruction and real-world language use, fostering more natural and effective communication. However, several challenges were identified, such as difficulty understanding fast-paced speech, unfamiliar cultural references, lack of structured guidance, and technical barriers like poor internet access and screen-related discomfort. The study highlights the importance of integrating authentic materials with appropriate scaffolding to maximise effectiveness. It also underscores the need for differentiated instructional strategies and infrastructure improvements to support diverse learner needs. By addressing the affordances and limitations of authentic materials, the study contributes valuable insights for curriculum developers, educators, and policymakers seeking to improve English language instruction in vocational education settings. The findings advocate for a more strategic and learner-centred incorporation of authentic materials to produce graduates with technical expertise and strong communicative competence for the global workforce.